The design of flood disaster monitoring dashboard for DKI Jakarta - Via Angelika; Tony Tony; Manatap Dolok Lauro (Journal of Intelligent Decision Support System (IDSS), 2023)
Disasters are events that threaten and disrupt the lives of living things caused by natural or non-natural factors or human actions resulting in human casualties, environmental damage, property losses, and psychological impacts. One of the natural disasters is flooding. This includes the disasters that often occur in the community in any area regardless of location and time. Flooding means excessive waterlogging, particularly those that often occur during the rainy season. The puddle arises due to increased water flow above the ground surface, either due to high rainfall or overflow of river water. Information on flood incidence is recorded daily in detail. This information allows flood incidence data to be made into a visualization. This dashboard is designed to display a dashboard that can show visualization of flood incident data. The data employed data on DKI Jakarta flood incidence from 2018 to 2021. The dashboard design used the prototyping method. Visualizing the data aims to facilitate users in accessing information about flood incidents in DKI Jakarta. The results obtained by the dashboard will display reports of an annual increase or decrease in flood incidents.